2002
DOI: 10.4049/jimmunol.169.10.5866
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Reactive Oxygen Species Generation by Rat Peritoneal Macrophages and Mast Cells Using the Highly Sensitive Real-Time Chemiluminescent Probe Pholasin: Inhibition of Antigen-Induced Mast Cell Degranulation by Macrophage-Derived Hydrogen Peroxide

Abstract: Mast cells and macrophages live in close proximity in vivo and reciprocally regulate one another’s function in various ways. Although activated macrophages possess a powerful reactive oxygen species (ROS) generating system, there is conflicting evidence regarding whether mast cells can produce ROS. We used the highly sensitive real-time chemiluminescent probe Pholasin to examine ROS release by peritoneal macrophages and mast cells isolated from OVA-sensitized rats. Macrophages stimulated with PMA (0.8 μM) or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
93
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 47 publications
8
93
0
2
Order By: Relevance
“…38) During inflammation, activated phagocytes such as neutrophils and macrophages generate an ROS-dependent respiratory burst, and ROS can orchestrate inflammatory responses. 40,41) Hence we also compared the LPSstimulated NO production with Anethum graveloens root and stem extracts for anti-inflammation effects. In the NO assays, the flower extract showed higher antiinflammation activity than the root and stem extracts (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…38) During inflammation, activated phagocytes such as neutrophils and macrophages generate an ROS-dependent respiratory burst, and ROS can orchestrate inflammatory responses. 40,41) Hence we also compared the LPSstimulated NO production with Anethum graveloens root and stem extracts for anti-inflammation effects. In the NO assays, the flower extract showed higher antiinflammation activity than the root and stem extracts (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…There are at least three potential sources of ROS within the irradiated lung, first that which is produced as a direct result of radiation, second that is generated by inflammatory cells [12,170], and third from the mitochondria because of leakage from the electron transport chain [14]. Using whole lung irradiation it is difficult to distinguish between these sources; however, previous studies in our lab using half lung irradiation of rats [27, 28, 119] showed significant DNA damage both in and out of the radiation field.…”
Section: Control Dietmentioning
confidence: 99%
“…Following radiation, type I cells are damaged and lost from the alveolar surface and type II cells rapidly proliferate to reepithelialize the alveolar surface. Type II cells may also be injured by radiation and this triggers a release of surfactant [11,12]. A large number of cytokines, growth factors and cytokines regulate this response [13].…”
Section: Pulmonary Response To Radiation Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are conflicting data regarding whether rat peritoneal mast cells actually can produce ROS. Swindle et al (24) claimed that the production of ROS observed in rat peritoneal mast cells is attributed to contaminating macrophages rather than to mast cells by themselves.…”
mentioning
confidence: 99%